2019
DOI: 10.3390/molecules24213923
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopy and Electrochemistry in Relation to DFT Computed Energies of Ferrocene- and Ruthenocene-Containing β-Diketonato Iridium(III) Heteroleptic Complexes. Structure of [(2-Pyridylphenyl)2Ir(RcCOCHCOCH3]

Abstract: A series of new ferrocene- and ruthenocene-containing iridium(III) heteroleptic complexes of the type [(ppy)2Ir(RCOCHCOR′)], with ppy = 2-pyridylphenyl, R = Fc = FeII(η5-C5H4)(η5-C5H5) and R′ = CH3 (1) or Fc (2), as well as R = Rc = RuII(η5-C5H4)(η5-C5H5) and R′ = CH3 (3), Rc (4) or Fc (5) was synthesized via the reaction of appropriate metallocene-containing β-diketonato ligands with [(ppy)2(μ-Cl)Ir]2. The single crystal structure of 3 (monoclinic, P21/n, Z = 4) is described. Complexes 1–5 absorb light strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Both HOMO and HOMO–1 were located on the iron center; however, experimentally it was found that the second oxidation of SubPcs 5 – 8 was assigned to be SubPc ring-based instead. Since it sometimes happens that orbitals can rearrange upon oxidation, it therefore is essential to optimize the cation (oxidized) species as well, in order to computaionally locate the locus of the second experimentally observed oxidation. The oxidized SubPcs 5 – 8 all showed that their LUMO is on the iron center (first oxidation) and the HOMO and HOMO–1 of the oxidized species both are on the SubPc-ring (second and third oxidation), in agreement with the experimental assignment; see Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Both HOMO and HOMO–1 were located on the iron center; however, experimentally it was found that the second oxidation of SubPcs 5 – 8 was assigned to be SubPc ring-based instead. Since it sometimes happens that orbitals can rearrange upon oxidation, it therefore is essential to optimize the cation (oxidized) species as well, in order to computaionally locate the locus of the second experimentally observed oxidation. The oxidized SubPcs 5 – 8 all showed that their LUMO is on the iron center (first oxidation) and the HOMO and HOMO–1 of the oxidized species both are on the SubPc-ring (second and third oxidation), in agreement with the experimental assignment; see Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Upon reduction of mer molecule 1, an electron is added to the LUMO of complex 1, which is of dx2-y2 character (Figure 3). This LUMO then becomes the HOMO of the reduced molecule 1, if no re‐arrangement of the frontier orbitals occurs during reduction [31–33]. This new HOMO of the reduced mer complex 1, also shown in Figure 3, now has dx2-y2 character, while the new LUMO of reduced complex 1, as well as LUMO+1 to LUMO+10, is ligand based.…”
Section: Resultsmentioning
confidence: 89%
“…This was nicely illustrated by the occupied molecular orbital of (Figure 3). This LUMO then becomes the HOMO of the [31][32][33]. This new HOMO of the reduced mer complex 1, also shown in Figure 3, now has d x 2 À y 2 character, while the new LUMO of reduced complex 1, as well as LUMO + 1 to LUMO + 10, is ligand based.…”
Section: Dft Optimized Geometry and Properties Of Moleculesmentioning
confidence: 82%
“…The higher-energy absorption bands below 300 nm are assigned to spin-allowed intraligand π–π* transitions (corresponding to ligand-centered states, 1 LC), while the lower-energy absorption bands between 300 and 540 nm are assigned to a mixture of metal-to-ligand charge transfers ( 1 MLCT and 3 MLCT). , Subsequently, absorption bands in the region 460–510 nm can be ascribed to the ferrocenyl moiety of complexes 2–5 and 10 . Absorption trends by these complexes deviated from the Beer–Lambert law, A = ε Cl , at concentrations greater than 30–40 μM, and may be the consequence of the onset of intermolecular associations.…”
Section: Results and Discussionmentioning
confidence: 99%